The Impact Of Current Fiscal Policy On Small And Medium Enterprises In The Kingdom Of Bahrain - et. al., Mohamed Hasan Ali Thabet, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In economies all around the world the small and medium enterprises (SMEs) play a major role in the development of the economies, this impact is especially shown in developing countries. SMEs are the most contributors to the economic development of the country and the creation of jobs in the economies worldwide. Therefore, the key aim of the current study was to measure the effect of the fiscal policy along with real interest rate and literacy rate on the growth of SMEs registered in the Kingdom of Bahrain. For this purpose, the time-series data of the last 20 years from 1998 to 2018 was collected from the world bank and the official government database. ADF unit root test was applied to check the stationary of the variables and the Ordinary Least Square (OLS) method was applied to analyze for further analysis as all the variables were found stationary at level. The regression results show that the fiscal policy and literacy rate has a positive impact on SME’s growth of the country; however, the real interest rate has a negative effect on SME’s growth. Based on the current findings, the study recommended that the government should spend more to develop the basic infrastructure to support the SME’s development as well as related education and training programs especially the technical education for small businesses.